Interferon Lambda: A New Sword in Cancer Immunotherapy - Ahmed Lasfar; Walid Abushahba; Murugabaskar Balan; Karine A. Cohen-Solal (Clinical and Developmental Immunology)
The discovery of the interferon-lambda (IFN-λ) family has considerably contributed to our understanding of the role of interferon not only in viral infections but also in cancer. IFN-λ proteins belong to the new type III IFN group. Type III IFN is structurally similar to type II IFN (IFN-γ) but functionally identical to type I IFN (IFN-α/β). However, in contrast to type I or type II IFNs, the response to type III IFN is highly cell-type specific. Only epithelial-like cells and to a lesser extent some immune cells respond to IFN-λ. This particular pattern of response is controlled by the differential expression of the IFN-λ receptor, which, in contrast to IFN-α, should result in limited side effects in patients. Recently, we and other groups have shown in several animal models a potent antitumor role of IFN-λ that will open a new challenging era for the current IFN therapy.